PERANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG JADI PADA CV. SUKSES SEJAHTERA DENGAN MENGGUNAKAN VISUAL STUDIO 2010 - Melisa Samosir; Rini Suwartika Kusumadiarti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This design aims to be able to manage finished goods inventory in a computerized way and present accurate reports for each period at CV Sukses Sejahtera. Data collection techniques were performed using observations, interviews and literature studies related to the finished product preparation information system at CV Sukes Sejahtera. The system development method used is cascade. The realization of this information system uses the Microsoft Visual Studio 2010 programming language with the database using MySQL. The difficulty faced by the company is that the registration of finished goods in stock is still done manually or has not been computerized, leading to delayed information on production results, difficulty in analyzing problems and often Frequent loss of finished product data. products. From this problem, the author deploys to the Finished Goods Inventory Information System using Microsoft Visual Studio 2010 so that the Inventory Report at CV Sukses Sejahtera is shown quickly and accurately. This research creates an app that simplifies and speeds dealers in recording finished goods stock.